Effects of inter-organism interactions in biofouling on microtopographic surfaces. Issue 6 (3rd July 2019) - Hoang, Trinh X.; Mai, Ha T. H.; Brennan, Anthony B.; Le, Ly
Abstract: An extended model of the surface energetic attachment (SEA) model is introduced to study the fouling of marine organisms on microtopographic surfaces, taking into account the excluded volume interaction and the attraction between the organisms. It is shown that the excluded volume interaction leads to changes in the site-typed attachment probabilities which increase with the average spore density on the surface. As a result of these changes, the spore density map is flattened under very high density fouling. The attractive interaction on the other hand leads to aggregation of spores and the average aggregate size increased with the strength of attraction. The model can be mapped to a specific experiment to determine the attachment energy parameters. In contrast to various prior empirical approaches, the extended SEA model is rigorous from the statistical mechanics viewpoint, thus it provides a reliable tool for studying complex attachment behaviors of microorganisms on topographic surfaces.